1984
DOI: 10.1177/001440298405100104
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Variables on Parental Perceptions of Staffings

Abstract: This study explored the relationship between parental satisfaction with special education IEP staffings and six variables. Together the six variables accounted for 78% of the variance in satisfaction. Simply allowing enough time for a staffing accounted for the most variance. In addition, the following three variables also had a statistically significant impact on satisfaction: (a) input from a number of people to formulate a good educational program, (b) attribution of blame to sources other than the parents,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…This parent perception is consistent with that of professionals who perceive a need for improved communication and cooperation to make the team process more effective (Fleming & Monda-Amaya, 2001;Gallagher & Malone, 2005). Both parent and professional contributions have been linked to parental satisfaction (Witt et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This parent perception is consistent with that of professionals who perceive a need for improved communication and cooperation to make the team process more effective (Fleming & Monda-Amaya, 2001;Gallagher & Malone, 2005). Both parent and professional contributions have been linked to parental satisfaction (Witt et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Other research has similarly indicated that parents are generally satisfied with team meetings, despite relatively low levels of participation (e.g., Goldstein, Strickland, Turnbull, & Curry, 1980;Witt, Miller, McIntyre, & Smith, 1984). According to Witt et al, sufficient parental participation results in greater parent satisfaction, but so do other factors, including sufficient meeting time, sufficient professional contribution to developing the IEP, and meetings with professionals who do not blame parents for their children's problems.…”
Section: Perceptions Of Team Meetingsmentioning
confidence: 99%
“…With the passage of PL 94-142, the expectation for parent involvement in the education of students with disabilities shifted from one in which parents were viewed as passive providers of information and acceptors of professional decisions to one in which they have been exhorted to participate actively with professionals in making the educational and service-related decisions that define their children's school programs (Hoover-Dempsey, Bassler, & Brissie, 1987;Turnbull & Turnbull, 1982;Witt, Miller, McIntyre, & Smith, 1984). More recently, conceptualizations of parent participation have been further expanded by amendments to the Education of the Handicapped Act (PL 101-476) which mandate that IEPs must specify needed transition services for students with disabilities.…”
Section: Involving Culturally Diverse Parents Ion Transition Planningmentioning
confidence: 99%
“…The results of these studies indicated little interExceptional Children action by parents when they attended the IEP meeting, with parents being perceived by school professionals as recipients of information. Despite this passive role, parents have generally been satisfied with the IEP conference and its outcomes (Witt, Miller, McIntyre, & Smith, 1984).…”
Section: Assumptions Of Iep Development When Inter-mentioning
confidence: 99%